The impact of celebrity endorsements in advertisements on Malaysian consumers’ purchasing intention: A parasocial interaction perspective - Tan, Sherene Yu Lin (2023)
The shift from traditional media towards online media, has made online advertisements gain much attention from both advertisers and consumers. With high saturation of advertisements online, consumers are facing a lack of interest which leads to marketers adopting the celebrity endorsement approach. There is still a lack of understanding on what factors determine the effectiveness of celebrity endorsements. The Parasocial Relationship Theory helps to shed some light as to why consumers respond well to celebrity endorsements. Nonetheless, the effect on consumer buying behavior needs to be further studied. Therefore, to tackle this gap, this study aims to investigate the factors that contribute to the effectiveness of celebrity endorsements in advertisements, to explore the degree of parasocial interactions (PI) between celebrities and consumers, and to investigate the impact of celebrity endorsements in advertisements and PI between celebrities and consumers on consumers’ purchasing behavior. A quantitative research method is adopted in this study and carried out by distributing online questionnaires to 50 respondents aged 18 to 30 years old in Klang Valley, Malaysia. This study found that factors of celebrity’s relation & compatibility and attractiveness & appeal affect the effectiveness of celebrity endorsements the most. Consumers do not show much forms of PI with celebrities they follow, but these interactions affect some of their purchasing behaviors such as buying products recommended by celebrities online. This study will serve to benefit researchers, marketers, and communication studies to have a clearer understanding of the factors which determine the effectiveness of celebrity endorsements, and the role or parasocial relationships on purchasing behaviors of Malaysians.